Be Your Sister’s Keeper: Personal Experience of Travelling a Lonely Journey in Academia - Mzindle, Duduzile (African Journal of Inter/Multidisciplinary Studies, 2024)
Neoliberal universities are farcical and absurd places where black women are marginalised intentionally or unintentionally to discourage them and others from significant accomplishments on the academic ladder. Black woman marginalisation takes variegated forms, and it has its roots in patriarchy and identity confusion. Whilst access is created by the system, there is very little support to enable black women to survive and succeed as they climb the bureaucratic ladder in neoliberal universities. The journey is worsened when one climbs the ladder and leaves sisters behind who choose to be ‘campers’ in these universities. Be your sister’s keeper is a biblical term that speaks to the fact that we need to practice ethics of care among ourselves. This is a qualitative self-study that I narrate my thirty-eight years of lived experiences, and it reflexively evaluates my lonely journey in academia. I use this platform to conscientise my African sisters about the challenges that they are likely to encounter in neoliberal universities. Caring for one another is an African term rooted in ‘ubuntu’ African philosophy that has prevailed over the ages. I argue that as black women, we need to create spaces where we can offer another not only a shoulder to cry on but encourage each other to navigate the academy and its mazes. I am convinced that my experiences and personal journey in academia add a voice to novice academics who must still navigate the bureaucratic ladder. I discuss cultural stereotyping and patriarchy, workplace oppression, and gender-based violence (GBV).